Stevens Johnson Syndrome in a patient with systemic lupus erythematosus on tuberculostatic treatment (Faculty of Medicine Universitas Indonesia, 2012)
A 22-year-old woman was admitted to the hospital because of 5-days history of redness and itch on her face. Additional complains were swelling on her feet, sore throat, and cough. Patient was on treatment for systemic lupus erythematosus and pulmonary tuberculosis (since 12 days). On physical examination, patient was alert, stable hemodynamic, anasarca edema, multiple purpuric macules lesion spread on her body, conjunctivitis of both eyes, multiple oral ulcers, erythema on genital mucosa. Laboratory results were anemia, leucopenia, hypoalbuminemia, proteinuria. We suspected this patient as Stevens Johnson syndrome due to tuberculostatic drugs. During treatment, we stopped the tuberculostatic drugs, and gave her parenteral methylprednisolone, with other supportive treatments. The patient was discharge after improvement of clinical condition and capable of self mobilization. (Med J Indones. 2012;21:235-9)